Biomimetic idealization of a mechanically coupled acoustic sound sensing mechanism. (February 2018) - Lee, Jin-Hyuk
This paper presents the idealization of a mechanically coupled acoustic sensor mechanism for directivity with the use of polysilicon, which has ideal mechanical and electrical material properties in terms of micro-fabrication. A mathematical model related to mechanical sensitivity is developed as a function of the material properties and geometry of the sensor, which evaluates the characteristics of a two-degree-of-freedom-based lumped parameter model. A challenge in such a study is that the model needs to be simple but sufficiently sophisticated to capture the characteristics of the sensor mechanism. Eigen modes and frequencies of the mechanically coupled acoustic sensor mechanism are determined by an energy method using mode functions applicable to the complete system that are from admissible the mode functions chosen for the component elements of the system. The synthesis is accomplished by using equations of constraint that follow conditions imposed by force equilibrium and deflection compatibility at the junctions. Finally, the results are compared with those obtained by a full-scale finite element model developed in a commercial software package. The predicted first and second natural frequencies differed by less than 10% and 3%, respectively, in all test cases.